Islamic Education Based on The Nature of Personality and The Potential of The Human Soul - Mulyadi Mulyadi (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
This article aims to examine philosophically, the values of Islamic education through the potential for self-reliance and the potential of the human soul. This is based on the view that the ideal concept in the field of education must be based on the potential of self and the potential of the human soul. This is because the basic purpose and objective of education is to form a complete (integral) human personality in accordance with human nature in developing the potential of the soul towards the level of piety to the Creator (Allah swt.). The findings of this article show that Western education is too focused on the sensory dimension and the study of material objects, thus neglecting other dimensions such as emotionality and spirituality. So we need an alternative concept of Islamic education that is able to meet the various dimensions of the soul starting from the senses, imagination, emotions, and spirituality. Human nature-based education is able to meet the essential needs of education because it considers all aspects of human personality and personality as biological beings as well as spiritual beings. Soul potential-based education can be an ideal education system because it pays attention to the education of the heart, mind, spirit and soul as a unity as well as the plurality of human personality. All potentials that are considered by Islamic education are integral to the purpose of humans being sent to the face of the earth, namely to become khalifatullah. The function is to provide peace for all creatures in the universe.Â